2004
DOI: 10.1159/000078497
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Determinants Controlling Homeostatic Recirculation and Tissue-Specific Trafficking of Lymphocytes

Abstract: The homeostasis of the immune system is maintained by the recirculation of naïve lymphocytes through the secondary lymphoid tissues, such as the lymph nodes, Peyer’s patches, and spleen. Upon insult by pathogens or antigens, lymphocytes become activated, and the regulated trafficking of these cells results in the integration of systemic and regional immune responses. The exquisite specificity of such lymphocyte trafficking is determined by tissue-specific guidance signals expressed by the endothelial cells of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 108 publications
(149 reference statements)
0
26
0
Order By: Relevance
“…There are now five different pieces of evidence favoring the idea that FasL expression in lymph node HEVs induces apoptosis in activated lymphocytes entering the lymph node parenchyma: (1) Activated lymphocytes are not able to migrate into lymph node parenchyma (Mackay 1991;Tanaka et al 2004); (2) In inactivating mutations of the Fas gene, both in mouse and in humans, lymph nodes are enlarged with paracortical expansion (Le Deist et al 1996;Sneller et al 1997); (3) HEVs express Fas ligand in the lymph node paracortex (Kokkonen et al 2004); (4) Most paracortical (near-HEV) apoptotic cells express Fas, as shown here; (5) Similarly, in immune-privileged sites, FasL in epithelium provides protection against the inflammatory process (Abbas 1996;Ferguson and Griffith 2006). About 50% of the germinal center apoptotic cells showed expression of CD20, a marker of mature Blymphocytes, and ?20% expressed CD19, a marker of immature B-lymphocytes, indicating that a majority of apoptotic cells in germinal centers are of B-lymphocyte lineage.…”
Section: Discussionmentioning
confidence: 99%
“…There are now five different pieces of evidence favoring the idea that FasL expression in lymph node HEVs induces apoptosis in activated lymphocytes entering the lymph node parenchyma: (1) Activated lymphocytes are not able to migrate into lymph node parenchyma (Mackay 1991;Tanaka et al 2004); (2) In inactivating mutations of the Fas gene, both in mouse and in humans, lymph nodes are enlarged with paracortical expansion (Le Deist et al 1996;Sneller et al 1997); (3) HEVs express Fas ligand in the lymph node paracortex (Kokkonen et al 2004); (4) Most paracortical (near-HEV) apoptotic cells express Fas, as shown here; (5) Similarly, in immune-privileged sites, FasL in epithelium provides protection against the inflammatory process (Abbas 1996;Ferguson and Griffith 2006). About 50% of the germinal center apoptotic cells showed expression of CD20, a marker of mature Blymphocytes, and ?20% expressed CD19, a marker of immature B-lymphocytes, indicating that a majority of apoptotic cells in germinal centers are of B-lymphocyte lineage.…”
Section: Discussionmentioning
confidence: 99%
“…Leukocyte trafficking is a dynamic multistep process of leukocyte rolling on the vascular endothelium, followed by activation, adherence, and transmigration into tissue (15,31,34,35,39,51,56,66,67). In particular, leukocyte recruitment into specific tissues is determined by integrin-mediated firm adhesion (2,7,20,31,33,39,42,43,46,73).…”
mentioning
confidence: 99%
“…L ymphocytes continuously recirculate between the blood and the lymph by way of the secondary lymphoid tissues, where Ags and APCs are selectively localized (1)(2)(3). To enter lymph nodes (LN) 3 and Peyer's patches (PP), lymphocytes in the blood selectively adhere to and transmigrate across high endothelial venules (HEV) in which certain lymphoid chemokines are constitutively expressed; these chemokines play a critical role in lymphocyte trafficking to the LNs and PPs (4 -7).…”
mentioning
confidence: 99%
“…To enter lymph nodes (LN) 3 and Peyer's patches (PP), lymphocytes in the blood selectively adhere to and transmigrate across high endothelial venules (HEV) in which certain lymphoid chemokines are constitutively expressed; these chemokines play a critical role in lymphocyte trafficking to the LNs and PPs (4 -7).…”
mentioning
confidence: 99%